2020
DOI: 10.1002/gcc.22910
|View full text |Cite
|
Sign up to set email alerts
|

NTRK and other recently described kinase fusion positive uterine sarcomas: A review of a group of rare neoplasms

Abstract: The landscape of uterine sarcomas has greatly expanded in recent years to include neoplasms with recurrent gene fusions, such as BCOR and YWHAE translocated high‐grade endometrial stromal sarcomas. Sophisticated molecular techniques have also resulted in the description of “new” entities associated with recurrent kinase fusions involving NTRK and RET as well as COL1A1‐PDGFB rearranged uterine sarcomas. These rare neoplasms will be discussed in this review, highlighting that some of the underlying molecular eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 76 publications
(105 reference statements)
2
58
0
Order By: Relevance
“…As this tumor was reported around the same time that NTRK ‐rearranged uterine spindle cell neoplasms were first described that diagnosis was not considered by the authors. Although there appears to be significant pathological overlap between this NTRK ‐rearranged IMT and NTRK ‐rearranged uterine spindle cell neoplasm, the latter generally lacks plasma cells, has at most a focal myxoid matrix, may be positive for S100 and CD34, and typically is ER and PR negative 11 . Furthermore, ETV6 has not yet been identified as a partner gene in NTRK‐ rearranged uterine spindle cell neoplasms, but has been reported in rare extrauterine IMTs 12,13 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As this tumor was reported around the same time that NTRK ‐rearranged uterine spindle cell neoplasms were first described that diagnosis was not considered by the authors. Although there appears to be significant pathological overlap between this NTRK ‐rearranged IMT and NTRK ‐rearranged uterine spindle cell neoplasm, the latter generally lacks plasma cells, has at most a focal myxoid matrix, may be positive for S100 and CD34, and typically is ER and PR negative 11 . Furthermore, ETV6 has not yet been identified as a partner gene in NTRK‐ rearranged uterine spindle cell neoplasms, but has been reported in rare extrauterine IMTs 12,13 .…”
Section: Discussionmentioning
confidence: 93%
“…Although there appears to be significant pathological overlap between this NTRK-rearranged IMT and NTRK-rearranged uterine spindle cell neoplasm, the latter generally lacks plasma cells, has at most a focal myxoid matrix, may be positive for S100 and CD34, and typically is ER and PR negative. 11 Furthermore, ETV6 has not yet been identified as a partner gene in NTRK-rearranged uterine spindle cell neoplasms, but has been reported in rare extrauterine IMTs. 12,13 Nonetheless, due to the rarity of spindle cell lesions with NTRK rearrangements, studies are warranted to further determine whether they represent a spectrum of the same disease vs distinct entities.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, these gene fusions are rare in common adult cancers (1,2). In gynecologic oncology, NTRK gene fusion is also rare, although there are several reports of uterine sarcoma with this fusion gene (4)(5)(6)(7). A previous cohort study showed that TPM3-NTRK1 is most frequent in NTRK1 fusions across multiple histologies (2).…”
Section: Introductionmentioning
confidence: 99%
“…As a vital target in the TLR signalling pathway, CD14 exerts a dual effect on oncogenesis, which can initiate several tumour-related signalling pathways or alter the immune microenvironment in the tumour [41]. COL1A1 was considered to be associated with the pathogenesis of COL1A1-PDGFB fusion uterine sarcoma [42]. DDR1 was reported as attending the development of cancer and fibrotic diseases [43].…”
Section: Discussionmentioning
confidence: 99%